2011
DOI: 10.1165/rcmb.2010-0401oc
|View full text |Cite
|
Sign up to set email alerts
|

Novel Murine Model of Chronic Granulomatous Lung Inflammation Elicited by Carbon Nanotubes

Abstract: Lung granulomas are associated with numerous conditions, including inflammatory disorders, exposure to environmental pollutants, and infection. Osteopontin is a chemotactic cytokine produced by macrophages, and is implicated in extracellular matrix remodeling. Furthermore, osteopontin is up-regulated in granulomatous disease, and osteopontin null mice exhibit reduced granuloma formation. Animal models currently used to investigate chronic lung granulomatous inflammation bear a pathological resemblance, but lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
98
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(116 citation statements)
references
References 44 publications
17
98
0
1
Order By: Relevance
“…Our previous MWCNT studies utilized trichrome staining but detected no fibrosis after instillation of MWCNT alone [10]. Trichrome staining in the current study revealed marked fibrotic changes within granulomas of mice receiving MWCNT + ESAT 6 (Figure 2D) as compared to granulomas of mice receiving only MWCNT (Figure 2C).…”
Section: Resultssupporting
confidence: 44%
See 4 more Smart Citations
“…Our previous MWCNT studies utilized trichrome staining but detected no fibrosis after instillation of MWCNT alone [10]. Trichrome staining in the current study revealed marked fibrotic changes within granulomas of mice receiving MWCNT + ESAT 6 (Figure 2D) as compared to granulomas of mice receiving only MWCNT (Figure 2C).…”
Section: Resultssupporting
confidence: 44%
“…C57BL/6J wild-type mice received an oropharyngeal instillation of MWCNT after sedation with isofluorane. MWCNTs (catalogue number 900–1501, lot GS1801, SES Research, Houston, TX) were freshly prepared and have been extensively described previously [10,22]. A single pulmonary instillation of MWCNT (100 μg) in PBS/35% surfactant (vehicle) ± ESAT-6 peptide 14 (NNALQNLARTISEAG) (20 μg) were delivered to wild-type C57Bl/6 mice.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations